1993
DOI: 10.1007/bf01955054
|View full text |Cite
|
Sign up to set email alerts
|

Acellular pertussis diphtheria-tetanus-pertussis vaccine containing separately purified pertussis toxoid, filamentous haemagglutinin and 69 kDa outer membrane protein as a booster in children

Abstract: In two double-blind, randomized, comparative studies involving a total of 218 children, an acellular pertussis (DTPa) vaccine containing diphtheria and tetanus toxoids and pertussis components filamentous haemagglutinin (FHA), pertussis toxoid (PT), and 69 kDa outer membrane protein (69 kDa OMP) was administered as a booster to 17-month-old and 5-year-old children with a history of routine whole-cell diphtheria-tetanus-pertussis (DTPw) vaccination. The control groups in these studies received DTPw vaccine. Amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Earlier studies [13][14][15][16][17][18][19] have demonstrated safety, good tolerability, and immunogenicity of acellular pertussis vaccines as booster doses in preschool children and adults. It is well known that adverse reactions to diphtheria-tetanus-pertussis immunization increase with age, additional doses, or both.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Earlier studies [13][14][15][16][17][18][19] have demonstrated safety, good tolerability, and immunogenicity of acellular pertussis vaccines as booster doses in preschool children and adults. It is well known that adverse reactions to diphtheria-tetanus-pertussis immunization increase with age, additional doses, or both.…”
Section: Discussionmentioning
confidence: 99%
“…Serum immunoglobulin G (IgG; antibodies to PT, FHA, and PRN were determined by an enzymelinked immunosorbent assay (ELISA), 13,15 which has a cutoff of 5 ELISA units(EU)/mL. Serum IgG antibodies to diphtheria and tetanus toxoids also were determined using ELISA, 21,22 which has a cutoff of .1 international units per milliliter (IU/mL).…”
Section: Serologic Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies [9][10][11][12][13][14][15][16] have demonstrated safety, and immunogenicity of DTPa vaccines as compared with DTPw vaccines when administered as booster doses in infants, preschool children and adults. Nevertheless, administration of the fifth dose of acellular vaccine in preschool children and adults has been associated with increased reactogenicity when compared to earlier doses of acellular vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…In one report, as compared to DT-vaccine, the relative frequencies (%) of these side-effects were (DTPw/DT) 37.4%/7.6% for local redness, 40.7%/7.6% for local swelling, 50.9%/9.9% for pain, 31.5%/14.9% for fever, 31.5%/14.9% for drowsiness, 53.4%/22.6% for fretfulness, 6.2%/2.6% for vomiting, 20.9%/7.0% for anorexia, and 3.1%/0.7% for persistent crying [9]. Reactogenicity is even much more pronounced in older children [19].…”
mentioning
confidence: 99%